How Luther became the reformer - Helmer, Christine (Westminster John Knox Press, 2019)
History and story: an introduction -- The experience of justification -- How Luther became the reformer -- Modernity and its contradictions -- A test case of anti-Judaism -- How Luther became the reformer (lowercase) of Catholicism -- Reformation.